An Inflammatory Polymorphisms Risk Scoring System for the Differentiation of Ischemic Stroke Subtypes - Elena Muiño; Jurek Krupinski; Caty Carrera; Cristina Gallego-Fabrega; Joan Montaner; Israel Fernández-Cadenas (Mediators of Inflammation)
Inflammation has been associated with atherothrombotic stroke and recently with cardioembolic stroke. Different genetic risk factors have been specifically associated with the subtypes of ischemic stroke (cardioembolic, atherothrombotic, and lacunar). However, there are no studies that have generated genetic risk scores for the different subtypes of ischemic stroke using polymorphisms associated with inflammation. Methods. We have analyzed 68 polymorphisms of 30 inflammatory mediator genes in 2,685 subjects: 1,987 stroke cases and 698 controls. We generated a genetic scoring system with the most significant polymorphisms weighted by the odds ratio of every polymorphism and taken into consideration the stroke subtype. Results. Three polymorphisms, rs1205 (CRP gene), rs1800779, and rs2257073 (NOS3 gene), were associated with cardioembolic stroke (p value <0.05). The score generated was only associated with the cardioembolic stroke subtype (p value: 0.001) and was replicated in an independent cohort (p value: 0.017). The subjects with the highest score presented a cardioembolic stroke in 92.2% of the cases (p value: 0.002). Conclusion. The genetics of inflammatory markers is more closely associated with cardioembolic strokes than with atherothrombotic or lacunar strokes. The genetic risk scoring system could be useful in the prediction and differentiation of ischemic stroke; however, it might be specific to particular ischemic stroke subtypes.